The sea officers: gentility and professionalism in the Royal Navy, 1775-1815 - Wilson, E (2014)
This thesis argues that British naval officers provide a useful category of analysis for social and cultural historians. While previous scholarship has largely ignored naval officers or treated them as equivalent, socially and professionally, to army officers or the traditional professions, the present study argues that the nature of service at sea presented challenges to officers' social status. Drawing on thousands of recently-digitized sources, as well as extensive archival materials, it explores the formation of naval officers' social identity, the forces that shaped their careers, and the changing landscape of social status at the end of the eighteenth century. The demands of life at sea placed naval officers in a liminal social space. Their claims to gentility were contingent and contested. They needed to be proficient in practical as well as theoretical skills. At the same time, officers were expected to be gentlemen. How officers shaped, and were shaped by, the changing definitions of that term provides the framework for the thesis. It makes three central contributions to the fields of British social and naval history. First, it emphasizes the continuing significance of social status boundaries in Georgian Britain. The existing literature misconstrues the chronology of the changing nature of gentility and misunderstands the relationship of naval officers to issues of gentility and professionalism. Second, it recalibrates our understanding of the nature and mechanisms of patronage networks. Social backgrounds made relatively insignificant contributions to shaping officers' careers; patrons used a much wider range of criteria when selecting clients. Finally, it questions the traditional separation of naval history from social and cultural history. The Navy and naval officers were central to British life at the end of the eighteenth century and cannot be effectively analysed separately. The Navy was both socially unique and uniquely important to Britain during the crisis of the Wars with Revolutionary and Napoleonic France.